Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/ptr.2855
|View full text |Cite
|
Sign up to set email alerts
|

Thylakoids suppress appetite by increasing cholecystokinin resulting in lower food intake and body weight in high‐fat fed mice

Abstract: Thylakoids are membranes isolated from plant chloroplasts which have previously been shown to inhibit pancreatic lipase/colipase catalysed hydrolysis of fat in vitro and induce short-term satiety in vivo. The purpose of the present study was to examine if dietary supplementation of thylakoids could affect food intake and body weight during long-term feeding in mice. Female apolipoprotein E-deficient mice were fed a high-fat diet containing 41% of fat by energy with and without thylakoids for 100 days. Mice fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 40 publications
8
58
3
Order By: Relevance
“…In a series of previous studies we have found that thylakoid membranes, the photosynthetic membrane in plant cells, inhibit pancreatic lipase/co-lipase in a dose-dependent way in vitro, an effect confirmed both in animal studies on rat 12 and mice 13 as well as in human studies 14,15 .…”
Section: The Effect Of Thylakoid Isolates On Lipolysis When Included supporting
confidence: 62%
“…In a series of previous studies we have found that thylakoid membranes, the photosynthetic membrane in plant cells, inhibit pancreatic lipase/co-lipase in a dose-dependent way in vitro, an effect confirmed both in animal studies on rat 12 and mice 13 as well as in human studies 14,15 .…”
Section: The Effect Of Thylakoid Isolates On Lipolysis When Included supporting
confidence: 62%
“…Reduced levels of leptin may suggest enhanced leptin sensitivity [65], which may stimulate fatty acid oxidation. Even thus, the present experiments have confirmed the ability to plant secondary metabolism of chlorophyll, caffeic acid, chlorogenic acid and polyphenol group which are available in C. nutans as well to decrease leptin levels and promote satiety signaling in healthy body [63]. Acetylcholinesterase (AchE) is an enzyme that hydrolyzes the neurotransmitter acetylcholine, producing choline and an acetate group [66].…”
Section: Citationsupporting
confidence: 75%
“…In addition, supplementation of thylakoid [63] and caffeic acid and chlorogenic acid [24] reduced serum leptin levels in mice. In the current study, Sakdarat et al [64] have been reported that three chlorophyll derivatives (phaeophytins) were extracted from C. nutans leaves, it was expected that thylakoid from plant chloroplasts are useful to elevated the satiety hormone cholecystokinin, which lead to reduce leptin levels [63]. Reduced levels of leptin may suggest enhanced leptin sensitivity [65], which may stimulate fatty acid oxidation.…”
Section: Citationmentioning
confidence: 98%
“…Further, there was an increase in lipase-colipase activity in thylakoid-treated animals compared to controls following binding of the membranes to the lipase-colipase complex. 95,100 Additionally, at the end of 100 days, there was a reduction in body fat, serum glucose, and free fatty acids; however, there was no change in PYY concentrations. There was a reduction in serum leptin which was consistent with the reduction in adipose tissue.…”
Section: Animal Studiesmentioning
confidence: 87%
“…There was a reduction in serum leptin which was consistent with the reduction in adipose tissue. 100 In another study, rats were fed a high-fat, low-fat, or thylakoid-supplemented high-fat diet for 32 days. While there was no change in energy intake, the rats in the thylakoid-supplemented group lost significantly more weight and percent body fat than the rats in the other groups.…”
Section: Animal Studiesmentioning
confidence: 99%